Molecular and Serological Examination of the Relationship of Human Herpesvirus 8 to Multiple Myeloma: orf 26 Sequences in Bone Marrow Stroma Are Not Restricted to Myeloma Patients and Other Regions of the Genome Are Not Detected - Tisdale, John F.; Stewart, A. Keith; Dickstein, Bruce; Little, Richard F.; Dubé, Ian; Cappe, D.; Dunbar, Cynthia E.; Brown, Kevin E. (Blood, 1998)
Human herpesvirus 8 (HHV-8) genomic sequences were recently detected by polymerase chain reaction (PCR) and in situ hybridization in bone marrow stromal cells grown from multiple myeloma (MM) patients, but not in cells from control subjects (Rettig et al, Science 276:1851, 1997). We sought to confirm these observations in our own group of MM patients (n = 30). DNA was extracted from adherent stromal cells grown under varying conditions and assayed for HHV-8 sequence using PCR to amplify the orf 26 (KS330) sequence (Chang et al,Science 266:1865, 1997), as initially reported. Samples from human control subjects (n = 25) were concurrently extracted and analyzed. After 30 cycles of amplification, we did not detect any positive samples. In a more sensitive nested PCR, samples from 18 of 30 (60%) MM patients were positive, at about the limit of detection, but orf 26 sequence was also amplified from 11 of 25 (44%) human control samples. However, PCR amplification from other regions of the viral genome (orf 72 and orf 75) was uniformly negative for all MM and control samples, despite equivalent sensitivity. Additionally, all sera from MM patients were negative for HHV-8 IgG by immunofluorescence. Our data do not support a role of HHV-8 in the etiology of MM but may suggest the presence of a related (KS330-containing) virus in MM patients and in some control subjects. This is a US government work. There are no restrictions on its use.